2005
DOI: 10.1159/000082595
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis for Abnormal Human Lung Development

Abstract: Our understanding of lung development in the past two decades has moved from an anatomical to a histological basis and, most recently, to a molecular basis. Tissue interactions specify tracheal and lung primordia formation, program branching morphogenesis of the airway epithelium and regulate epithelial differentiation. In addition, lung development is influenced by mechanical and humoral factors. The regulatory molecules involved in morphogenetic signaling include growth and transcription factors and extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 278 publications
(185 reference statements)
1
40
0
1
Order By: Relevance
“…Our study suggests that some of the molecular factors that may be involved in generating pulmonary hypoplasia are likely to affect vascular development, exacerbating clinical hypoxemia, the lethal common denominator in this disorder. Other human congenital malformations of the lung that involve pulmonary vascular anomalies (for example alveolar-capillary dysplasia) (Cullaine et al, 1992) are poorly understood molecularly (Groenman et al, 2005). The findings described here may provide an insight into the etiology of these often lethal, congenital diseases.…”
Section: Developmentmentioning
confidence: 68%
“…Our study suggests that some of the molecular factors that may be involved in generating pulmonary hypoplasia are likely to affect vascular development, exacerbating clinical hypoxemia, the lethal common denominator in this disorder. Other human congenital malformations of the lung that involve pulmonary vascular anomalies (for example alveolar-capillary dysplasia) (Cullaine et al, 1992) are poorly understood molecularly (Groenman et al, 2005). The findings described here may provide an insight into the etiology of these often lethal, congenital diseases.…”
Section: Developmentmentioning
confidence: 68%
“…Notable among these are members of the TGF-b family of peptide growth factors, which are also key regulators of late lung development (45). Recently, excessive TGF-b activity has been identified as a key pathogenic factor in animal models of BPD (20,22,46), which suggested that dysregulated TGF-b signaling might underlie the aberrant expression of lysyl oxidases in BPD. Indeed, dampening of TGF-b signaling in the newborn lung injury model used in this study reduced the expression of the lox gene, although expression of other members of the lysyl oxidase family was unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Lung development begins at 3-4 weeks of gestation and occurs in six stages: the embryonic stage (4-7 weeks), pseudoglandular stage (5-17 weeks), canalicular stage (16-26 weeks), saccular stage (24-38 weeks), alveolar stage (36 weeks of gestation to 2 years of life) and microvascular maturation (birth to 2-3 years of age)[25,26,27]. Morotti et al [13,14] postulated that CPAM is caused by a focal arrest in lung development at different stages of the branching of the bronchopulmonary tree: the first subtype (CPAM bronchiolar types I, II and III) at the pseudoglandular stage and the second subtype (CPAM type IV) at the saccular stage.…”
Section: Histopathology and Geneticsmentioning
confidence: 99%